Uses of Digital Mediation in the School-Families Relationship During the COVID-19 Pandemic - León-Nabal, Blanca; Zhang-Yu, Cristina; Lalueza, José Luis (Frontiers in Psychology, 2021)
The COVID-19 pandemic has sharpened the inequalities in our societies. In Spain, we observed that the impact on schooling varied according to socioeconomic, gender and sociocultural variables (González & Bonal, 2020). In this article, we present a case analysis illustrating the impact of the COVID-19 pandemic on schooling in early educational grades (ages 3-6), which leads us to focus on school-family relationship. First, we present some studies that show the inequalities in education during the lockdown period, the digital divide faced by both schools and families and how digital mediation impacts school-family relationships. Then we will introduce our study, which aims to explore the uses, potentials and limitations of an app intended to facilitate the relationship. Our study took place during September 2020-January 2021, when social restriction persisted. It took the form of a telematic ethnography in which we monitored the meetings of the Early Childhood Education teachers and their interaction with the families via an app-based communication tool. Results have allowed us to identify that most conversations are initiated by the school and their aim is to show families the classroom activities. We have also observed some advantages regarding the use of this app: communication can become more direct and immediate, and teachers have developed strategies to foster proximity in this relationship, as well as to respond inclusively to diversity. Regarding the challenges, we identified the lack of involvement of some families, the need to transform the roles played by families and children, and the difficulty to maintain personalized relationships.